Development of Marriage Learning model in Islam through Project Based Learning in Higher Education - Eddy Saputra; Nur Ali; Fery Rahmawan; Achmad Muhajir; Ahmad Mujib (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
Lack of understanding of responsibility and commitment means that marriage is no longer in a holy and sacred position. Learning about the Islamic religion, especially in the chapter on marriage, is not sufficient provision to provide an understanding of how to build commitment. In the marriage material, graduation in the course is only 30% of the total number of students, this is because the learning model used still uses the conventional model. In an effort to minimize the loss of commitment to marriage, a learning strategy is needed by developing a learning model with project-based learning that aims to increase students' understanding of the material on marriage in Islam. The research aims to ensure that religious learning in public universities can increase understanding of marriage and reduce the number of divorces in marriage. This research uses a qualitative approach using the research and development method, namely developing a learning model to make it more interesting so that the material presented can be properly understood by students. The findings of the research results show that the development of the model carried out can increase the graduation rate to 100%. The model developed can answer the needs of learning Islamic religion in public universities. Keywords:  Model Development, Marriage in Islam, Project Based Learning